A combined NMR, MD and DFT conformational analysis of 9-O-acetyl sialic acid-containing GM3 ganglioside glycan and its 9-N-acetyl mimic. (29th April 2020) - Li, Wanqing; Battistel, Marcos D; Reeves, Hannah; Oh, Lisa; Yu, Hai; Chen, Xi; Wang, Lee-Ping; Freedberg, Darón I
Abstract: O -Acetylation of carbohydrates such as sialic acids is common in nature, but its role is not clearly understood due to the lability of O -acetyl groups. We demonstrated previously that 9-acetamido-9-deoxy- N -acetylneuraminic acid (Neu5Ac9NAc) is a chemically and biologically stable mimic of the 9- O -acetyl- N -acetylneuraminic acid (Neu5, 9Ac2 ) of the corresponding sialoglycans. Here, a systematic nuclear magnetic resonance (NMR) spectroscopic and molecular dynamics (MD) simulation study was undertaken for Neu5, 9Ac2 -containing GM3 ganglioside glycan (GM3-glycan) and its Neu5Ac9NAc analog. GM3-glycan with Neu5Ac as the non- O -acetyl form of Neu5, 9Ac2 was used as a control. Complete 1 H and 13 C NMR chemical shift assignments, three-bond 1 H- 13 C trans-glycosidic coupling constants ( 3 J CH ), accurate 1 H- 1 H coupling constants ( 3 J HH ), nuclear Overhauser effects and hydrogen bonding detection were carried out. Results show that structural modification ( O - or N -acetylation) on the C-9 of Neu5Ac in GM3 glycan does not cause significant conformational changes on either its glycosidic dihedral angles or its secondary structure. All structural differences are confined to the Neu5Ac glycerol chain, and minor temperature-dependent changes are seen in the aglycone portion. We also used Density Functional Theory (DFT) quantum mechanical calculations to improve currently used 3 J HH Karplus relations. Furthermore, OH chemical shifts were assigned at −10°C and no evidence of an intramolecular hydrogen bond was observed. The results provide additional evidence regarding structural similarities between sialosides containing 9- N -acetylated and 9- O -acetylated Neu5Ac and support the opportunity of using 9- N -acetylated Neu5Ac as a stable mimic to study the biochemical role of 9- O -acetylated Neu5Ac.